2018
DOI: 10.21521/mw.6137
|View full text |Cite
|
Sign up to set email alerts
|

Variability of morphological characteristics of middle-European bees of the ‘Northern M’ line

Abstract: The aim of the study was to evaluate the variability of morphological characteristics of native middle-European bees (Apis m. mellifera) of the ‘Northern M’ line. The research covered characteristics of breed (the length of proboscis, the cubital index), body size (the width of tergite 4 and the sum of widths of tergites 3 and 4) and wing size (length and width). The study compared bees harvested from a leading apiary and from collaborating apiaries participating in a program for the protection of genetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…These outcomes align with Bakr ( 2008) findings, where a 2% biochar inclusion resulted in higher chick feed intake, BWG, and FCR. Similar benefits were observed in broiler chicks with up to 1.0% inclusion of maize cob biochar (Kana et al, 2011), as well as in studies utilizing hardwood biochar Zaborowski, 2003 andMajewska et al, 2011). El-Ghalid et al (2022) who found that treatment groups that added BC levels of 1, 2, 4, and 6 % outperformed the control group in terms of productivity, EEF, and production index.…”
Section: Results and Discussion Productive Performancesupporting
confidence: 62%
“…These outcomes align with Bakr ( 2008) findings, where a 2% biochar inclusion resulted in higher chick feed intake, BWG, and FCR. Similar benefits were observed in broiler chicks with up to 1.0% inclusion of maize cob biochar (Kana et al, 2011), as well as in studies utilizing hardwood biochar Zaborowski, 2003 andMajewska et al, 2011). El-Ghalid et al (2022) who found that treatment groups that added BC levels of 1, 2, 4, and 6 % outperformed the control group in terms of productivity, EEF, and production index.…”
Section: Results and Discussion Productive Performancesupporting
confidence: 62%
“…Even though we have a number of methods, the conventional morphological evaluation has not become any less important. Researchers still value the method and use it willingly [ 40 , 42 , 45 ]. Note that the standard morphological method makes it possible not only to reliably measure such features as the body size or proboscis length but also to track the diversification of such features.…”
Section: Introductionmentioning
confidence: 99%